Analysing the two-level game: international and national determinants of change in education policy making - Kathrin Leuze; Tilman Brand; Anja P. Jakobi; Kerstin Martens; Alexander-Kenneth Nagel (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2008)
Education policy making is often considered an exclusive domain of the nation state in western industrialised countries. Since the 1990s, however, international organisations (IOs) have started to play a greater role in the field of education by developing new forms of governance. As a consequence, the predominance of the nation state in education becomes an increasingly contested issue. Yet, it is not clear what kind of effects IO governance will have, whether it brings about greater convergence among national education policies by promoting uniform solutions for commonly shared problems, or whether national institutions continue to follow their own logic, thereby hindering equal responses to IO governance. In order to develop a better understanding of the dynamics in this two-level game, this paper sets out to develop an analytical framework for examining the interplay between international and national determinants of change in the field of education. We argue that IOs apply different governance instruments by which they seek to influence national education policy making. However, the degree to which nation states will respond to these international stimuli is likely to be mediated by national transformation capacities, most prominently veto players and nationally rooted ideas of education. Based on these basic assumptions, we develop a parsimonious model in which we assess the influence of IO governance on national education policy making mediated through national transformation capacities. – – Bildungspolitik wird in den westlichen Industrienationen häufig als ausschließliche Aufgabe des Nationalstaates betrachtet. Seit den 1990ern ist jedoch zu beobachten, dass internationale Organisationen (IOs) eine immer größere Rolle im Politikfeld Bildung spielen, indem sie neue Formen der Governance entwickeln. Dies führt dazu, dass die staatliche Vorherrschaft in der Bildungspolitik zunehmend in Frage gestellt wird. Dennoch ist bisher unklar, welche konkreten Effekte der Einfluss internationaler Organisationen hat. Zum einen wäre es möglich, dass sie einheitliche Lösungen für Probleme im Bildungsbereich vorschlagen, die von vielen Nationalstaaten geteilt werden, was zu einer größeren zwischenstaatlichen Konvergenz der Bildungspolitik führen könnte. Zum anderen wäre denkbar, dass nationale Institutionen ihrer eigenen Logik folgen, was eine Annäherung nationaler Pfade verhindern würde. Um ein besseres Verständnis der Dynamiken in diesem Zwei-Ebenen-Spiel zu ermöglichen, soll in diesem Arbeitspapier ein analytischer Rahmen entwickelt werden, anhand dessen das Zusammenspiel der nationalen und internationalen Determinanten von Wandel in der Bildungspolitik untersucht werden kann. Es wird angenommen, dass IOs mit Hilfe verschiedener Governance Instrumente versuchen, nationale Bildungspolitik zu beeinflussen. Allerdings reagieren Nationalstaaten nicht zwangläufig uniform auf diese internationalen Stimuli, sondern entsprechend ihrer Transformationskapazitäten. Diese werden hauptsächlich von nationalen Vetospielern und nationalen Leitideen von Bildung beeinflusst. Aufbauend auf diesen Annahmen entwickeln wir ein einfaches Modell zur Analyse des Wandels von Bildungspolitik, der durch IO Governance ausgelöst und durch nationale Transformationskapazitäten gesteuert wird.
Keywords: 330